The Russo-Ukrainian Selected War Images: A Semiotic Study of War Photography on CNN’s Website - Asst. Lect. Anmar Ahmed Kadhem; Prof. Hussain Hameed Mayuuf (Journal of College of Education, 2024)
The Russo-Ukrainian war is a highly complex issue, since it is a long-period conflict and because of the sensitivity of the regional, and international situations. War photography occupies a countable area in war discourse. In this conflict, it is exploited by American news channels, like CNN to reproduce unipolarity by covering one side of truth and by passing ideological messages. Starting from visual social semiotics and its usefulness in dealing with and analyzing images, the study adopts Kress and Van Leeuwen’s (2006) model of visual grammar to analyze three war photographs from the website of CNN. The results of the study show that the images are dedicated to the Ukrainians only and to express their conditions. It also shows that the visual meanings are used ideologically against the Russians.